Gingyo Gedokusan vs Oseltamivir for the Treatment of Uncomplicated Influenza and Influenza‐like illness: An Open‐label Prospective Study - Iwata, Kentaro; Igarashi, Wataru; Honjo, Midori; Nishimoto, Takashi; Shinya, Kyoko; Makino, Akiko; Mitani, Kazuo; Tatsumi, Yoshiko; Ninomiya, Hiroyuki; Higasa, Kumi; Usuki, Seiichiro; Kagawa, Hiroki; et al. (General medicine (Saga-shi, Japan), 2013)
Background Gingyo‐gedoku‐san (GGGS) is an herbal medicine approved for upper respiratory infections in Japan. We conducted an open‐label, multi‐center, prospective trial, comparing GGGS with oseltamivir in patients with influenza and influenza‐like illness (ILI) as a pilot study. Methods Subjects were healthy persons aged between 16 and 40, and were enrolled from January 12, 2010 to March 24, 2011. Fifteen patients were enrolled in this trial (8 and 7 for GGGS and oseltamivir, respectively). RT‐PCR was positive for pandemic influenza A (H1N1) in 10 patients. The patients were provided with either GGGS or oseltamivir for 5 days. The primary outcome was mortality and/or hospitalization 7 days after the initial diagnosis. Body temperature and other clinical characteristics were also evaluated. Results All patients recovered from illness without complication or hospitalization. The mean time to resolve symptoms for the GGGS and oseltamivir groups was 3.9 days and 3.3 days, respectively (p = 0.43). The GGGS group appeared to have a smaller symptom score AUC than the oseltamivir group, (p = 0.26). Time to recover activity level appeared to be shorter in the GGGS group (p = 0.10), with shorter time to recover health status (p = 0.02). Subgroup analysis on patients with positive PCR showed similar results between the two groups. Conclusion GGGS was associated with symptom improvements resembling oseltamivir for both influenza and ILI. Randomized controlled trials involving larger sample sizes are needed to confirm these results.